Creating a Euro Area Safe Asset without Mutualizing Risk (Much) - Álvaro Leandro; Jeromin Zettelmeyer (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper explains and evaluates three proposals to create “safe assets” for the euro area based on sovereign bonds, in which sovereign risk is limited through diversification and some form of seniority. These assets would be held by banks and other financial institutions, replacing concentrated exposures to their own sovereigns. The paper focuses on three ideas: (1) to create multitranche “sovereign bond-backed securities” (SBBS), of which the senior tranche would constitute a safe asset; (2) to create a senior, publicly owned financial intermediary that would issue a bond backed by a diversified portfolio of sovereign loans (“E-bonds”); and (3) to issue sovereign bonds in several tranches and induce banks to hold a diversified pool of senior sovereign bonds (“multitranche national bond issuance”). Public attention (including public criticism) has so far focused on the first idea; the other two have not yet been seriously debated. We find that none of the competing proposals entirely dominates the others. SBBS do not deserve most of the criticism to which they have been subjected. At the same time, E-bond and multi-tranche national bond issuance have several interesting features—including inducing fiscal discipline—and warrant further exploration.
Keywords: F33; F36; G21; H63; 330; safe assets; sovereign debt; banking crisis; euro crisis; eurobonds; ESBies; SBBS; E-bonds